Cultural aspects that influence the associative work of agricultural production chains in the Mantaro Valley of Peru - Rodríguez Giráldez, Wiliam Pedro (2020)
The purpose of this research was to determine how cultural aspects or beliefs of agricultural producers such as collectivism, trust, formality in land titling and productive planning influence the associative work of agricultural productive chains. Considering that for many years productive chains have been promoted as a development alternative for small agricultural producers in the Mantaro Valley, they have received training services, technical assistance, market articulation, etc., but very few remain today. The applied and descriptive research was carried out from July 2016 to May 2017 with the participation of 383 agricultural producers from four provinces of the Mantaro Valley, Junín, Peru. The results obtained show that the factors of trust and productive planning directly influence the associative work, while the aspects of collectivism and formality do not influence.